Pneumococcal Bacteremia Presenting as Acute Parotitis and Sepsis. (10th September 2009) - Kataria, Ashish; Multz, Alan S.
Abstract : We report a case of a 33-year-old female with history of Systemic Lupus Erythematosus (SLE) presenting with acute febrile illness and unilateral parotid gland enlargement progressing to septic shock. The chest imaging showed bilateral multilobar infiltrates and Pneumococci were identified in the blood cultures. The patient was treated with broad-spectrum antibiotics. The underlying imunosupression caused by SLE and long-term steroid treatment could have predisposed this patient to invasive Pneumococcal disease.